Peningkatan Hasil Belajar Matematika dengan Menggunakan Metode Subtraction Plus One di MIN 6 Gunungkidul - Musiran (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve students' learning outcomes in Math subjects using subtraction plus one method. This research uses class action research methods including planning, implementation, observation, and reflection activities. The study subjects are grade III-A MIN 6 Gunungkidul students in the 2019/2020 school year. Data is taken through observations, documentation, and tests. The results of the analysis showed an increase in each cycle. In cycle II, students scored above KKM as many as 19 students or about 83.6% with an average score of 83.6. Subtraction Plus One method can improve the math learning results of students in grade III-A MIN 6 Gunungkidul.